ANALISIS APLIKASI QUIZIZZ SEBAGAI MEDIA EVALUASI PEMBELAJARAN IPA PADA MATERI ORGAN GERAK MANUSIA - Setiawulan Prihantini, Alifah; Harlinda Syofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of media use in science learning evaluation activities, teachers still rely on simple media such as paper media for providing practice questions so that students find it difficult to understand the images displayed on paper because the images on the questions are not clearly visible. Lack of knowledge about the types of interactive media is one of the factors that teachers still use simple media and teachers who are less competent in applying technology properly are one of the reasons teachers still use paper media in science learning evaluation activities. This study aims to describe the analysis of the Quizizz application as a science learning evaluation media. This study is a descriptive qualitative study that describes and analyzes in depth the features contained in the Quizizz application and describes the procedures for using the Quizizz application as a learning evaluation media. The data collection technique uses a documentation study, most of which is research data in the form of images regarding the features of the Quizizz application. The results of the study show that there are many features in Quizizz that can be utilized by teachers as a medium in evaluating science learning, there are 12 types of question maker features that can be accompanied by images, various features can make it easier for teachers to share practice questions practically and efficiently so that the Quizizz application is worthy of being utilized and used by teachers as a medium in evaluating science learning.